2017
DOI: 10.1177/1708538117707612
|View full text |Cite
|
Sign up to set email alerts
|

Fluid displacement from intraluminal thrombus of abdominal aortic aneurysm as a result of uniform compression

Abstract: Objectives The results after aneurysm repair with an endovascular aneurysm sealing (EVAS) system are dependent on the stability of the aneurysm sac and particularly the intraluminal abdominal aortic thrombus (ILT). The postprocedural ILT volume is decreased compared with preprocedural ILT volume in aortic aneurysm patients treated with EVAS. We hypothesize that ILT is not stable in all patients and pressurization of the ILT may result in displacement of fluids from the ILT, no differently than serum is displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Displacement in aneurysms generates instabilities which may lead to its rupture [8]. On simulations, the greatest instability occurs when the thrombus is not taken into account, with a displacement value of 3.7210 -4 ± 2.0010 -4 mm, followed by an aneurysm when the blood flows through the wall 5.9610 -5 ± 3.2110 -5 mm and of the aneurysm with the thrombus with 6.1010 -5 ± 3.2910 -5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Displacement in aneurysms generates instabilities which may lead to its rupture [8]. On simulations, the greatest instability occurs when the thrombus is not taken into account, with a displacement value of 3.7210 -4 ± 2.0010 -4 mm, followed by an aneurysm when the blood flows through the wall 5.9610 -5 ± 3.2110 -5 mm and of the aneurysm with the thrombus with 6.1010 -5 ± 3.2910 -5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that intraluminal thrombus cannot be addressed as a rigid structure and might change over time. [11][12][13] This spongelike effect in combination with a larger AAA diameter might result in bending of the stent frames into the thrombus and parting of the stent frames, which can make the EVAS configuration unstable. A low amount of polymer surrounding the stent frames in small flow lumens might also induce instability into the EVAS configuration.…”
Section: Discussionmentioning
confidence: 99%